Papua New Guinea: Country Report on Human Rights - Talao, Freda (Victoria University of Wellington Law Review, 2009)
This article provides an overview of Papua New Guinea (PNG)'s status on human rights. The author explores the human rights treaties that PNG has ratified, the available legal and administrative remedies for human rights breaches, the principle of the rule of law in PNG, and the culture and language of PNG. It is concluded that PNG has not made much progress in advancing or protecting the rights of its people, and must support all initiatives to educate people on their rights as a strategy to ensure that the people are not left continuously ignorant of human rights issues.